PERAN ARTIFICIAL INTELLIGENCE DAN TATA KELOLA DALAM MENGATASI PENYELUNDUPAN PAJAK YANG MERUGIKAN NEGARA - Laola Marda; Renē Johannes (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
This study aims to determine what factors can cause tax evasion actions, both from the taxpayers themselves and government policies that have been implemented, including the possibility to implement artificial intelligence in the near furure dan good governance. The method used in this study is a descriptive method by using secondary data, data sourced from the literature with the aim of collecting relevant information and sources. Knowing the factors that cause tax evasion actions by conducting keyword searches, subject searches, scientific citation searches, books, scientific articles, research reports, sources, and documents related to research. The results of this study indicate that there are two main factors that cause tax evasion actions, namely the effectiveness of the implementation of the self-assessment system, and government policies in regulating the amount of applicable tax rates as a benchmark for the value of tax payments.Keywords: Artificial Intelligence, Good Governance, Self Assessment System, Tax Evasion